Unveiling the developmental and tumor-suppressive roles of the p53 variant p53psi - Chiara Gorrini; Soode Jafari; Gordon Duncan; Bryan Snow; Liam Hendrikse; Louis McLoughlin; Jillian Haight; Andrew Wakeham; Chantal Tobin; Andrew Elia; Paramesh Ramachandran; Rhoda Law; et al. (Proceedings of the National Academy of Sciences, 2026)
Through alternative splicing, the TP53 gene can generate multiple protein isoforms with distinct biochemical properties. The p53psi isoform has been identified as a shorter variant than full-length p53 as it lacks nuclear localization, oligomerization, and part of the DNA binding domains due to the use of an alternative 3’ splice site in intron 6. Several TP53-truncating mutations, including those producing p53psi, have been detected in a significant proportion of human tumors. However, the mechanistic roles of these truncated p53 proteins remain poorly understood. Here, we describe the generation and analysis of a genetically engineered mouse model that expresses the p53psi protein in place of the full-length p53 protein. In the C57/BL6J genetic background, mice heterozygous for the targeted p53psi allele (p53 KI/+ ) appear phenotypically normal, survive to adulthood, and reproduce. However, heterozygote matings fail to yield viable p53psi homozygote knock-in (p53 KI/KI ) pups, indicating that forced p53psi expression disrupts embryogenesis. Timed matings revealed that homozygous p53psi expression is embryonically lethal on day E16.5. E14.5-16.5 embryos were pale, reduced in size, and exhibited exencephaly, a defect typically associated with neural tube closure failure. Mouse embryonic fibroblasts (MEFs) derived from p53psi embryos and transformed with the E1A and H-RasV12 oncogenes formed tumors with a decreased growth rate compared to their p53 null counterparts, suggesting that p53psi retains at least some tumor-suppressive functions. Our mechanistic studies suggest that p53psi modulates tumorigenesis by triggering senescence. These findings provide insights into the role of the p53psi variant, paving the way for a better interpretation of TP53 mutational patterns in human cancers.